Structural complexity of mangroves in Playa Blanca, Escondido and Rincón de Osa, Golfo Dulce, Costa Rica. - Samper-Villarreal, Jimena; Silva-Benavides, Ana Margarita (Revista de Biología Tropical, 2015)
This study reports the structural characteristics and distribution of species in the mangrove forests of Playa Blanca, Escondido and Rincón de Osa in Golfo Dulce, South Pacific of Costa Rica. Multiple lineal transects were carried out at each of the mangrove forests. Every 10 meters along each transect the diameter at breast height, basal area, and height was determined for all mangrove trees within a 5x5meter square plot. Sediment and interstitial water (salinity) samples were also collected at each plot. Total density of the stand was determined, as were the density of each mangrove species, the importance value and basal area per species, and general complexity indices for each mangrove forest. The dominant species at all three mangroves were Rhizophora racemosa and Pelliciera rhizophorae. Forest structure was more similar between Playa Blanca and Rincón mangroves than with Escondido. Playa Blanca was the forest with the tallest canopy height and lowest density, while Escondido had the highest density and the shortest canopy height. Escondido was also the forest with the least number of species and the only one where Conocarpus erectus was present. Species composition and dominance at these mangroves coincides with that reported for the region. However, the variation in structure and complexity among the three mangroves is greater than the commonalities with mangroves in the region. Topographical and historical analysis of these mangroves could further elucidate the present structure and complexity variation among them.